Classification and mapping of the glaciers on Axel Heiberg Island using TerraSAR-X SAR data - Hauser, Sarah (2021)
Global warming led to an increase in the global average temperature of ~ 1.0 °C between pre-industrial times and today. Glaciers, ice caps and ice sheets are sensitive indicators of these changes. The decrease in land ice masses, which are the world's largest freshwater reservoirs, is already having a strong impact on human life on Earth and is likely to increase in the future. As a result, glacial nature hazards may increase, global water storage may be affected, but also biodiversity may be impacted. The rise in global sea levels, the latter of which has already accelerated significantly in recent decades, can also be attributed to global glacier melt. Monitoring of the behaviour of glacial systems and their response to climatic changes is therefore of great importance. Given the large areal coverage, temporal variability, inaccessibility and remote location of many snow-covered regions, remote sensing is ideal for monitoring the glaciers and its trends at both spatial and temporal scales. Whereas optical remote sensing data has a long history in monitoring glaciers, data from optical sensors can be affected by cloud cover as well as (polar) darkness. Synthetic Aperture Radar (SAR) however, is a valuable alternative as it is independent of clouds and illumination conditions. This work aimed to identify the glacial zones on Axel Heiberg Island using multitemporal TerraSAR-X data over a period from 2017 to 2020. This is achieved based on an analysis of the backscatter behaviour of the SAR signal. In order to obtain plausible results, optical (Sentinel-2) satellite images, a digital elevation model, as well as climatological data, are used. Seasonal melting and refreezing patterns have been detected, matching to an extent climatological data, in particular the local temperatures. Overall, there is a positive trend, a continuous increase, in temperatures. This is reflected in the zonal glacier changes, in the warmer years, more extensive melt zones are detected in terms of time and area. In addition, glacier flow ...